Non-reporting of sexual violence as action: acts, selves, futures in the making. Issue 1 (2nd January 2021) - Hansen, Maria; Stefansen, Kari; Skilbrei, May-Len
ABSTRACT: Individual, cultural and structural barriers exist in reporting rape to the police. Our study's context is Norway, where reporting is more accepted than before and is even encouraged. Still, few who experience rape report the incident. Based on qualitative interviews we examine how women who refrain from reporting rapes give their choice meaning. We draw from Boltanski and Thévenot's version of cultural sociology, especially the idea that meaning-making in concrete situations relates to wider 'regimes of justification': particular framings that render choices and interpretations intelligible. The aftermath of rape leaves women with having to balance their own and others' needs and expectations. In talking about the rape and how they afterwards manoeuvre to reconcile conflicting norms and needs, the women activate two different regimes of justification; an instrumental and an ontological. They negotiate between expectations set out in an instrumental regime of justification, focusing on acts and actions, and a more ontological regime of justification, wherein focus lies on their sense of self and future identities. They position themselves as 'evolving selves', a position from where they are able to prevent further ruptures by deploying a developmental logic rather than answering the call to 'do the right thing' and report.